POTENTIALS FOR DEVELOPMENT OF RURAL TOURISM IN BAČKI PETROVAC MUNICIPALITY - Pejanović, Radovan; Demirović, Dunja; Đorđević, Jamina; Radović, Gordana (Economics of Agriculture, 2014)
The main goal of this paper is to prove the assumption that in the municipality of Bački Petrovac there is a predisposition for the development of rural tourism, taking into consideration the existing Spatial plan of the municipality, its conception and planning priorities. The analysis of internal and external preconditions for the development of tourism was conducted and also a fled survey of registered rural households. Results of the analysis show that the external features do not represent a significant obstacle to the development of tourism, while on the other hand internal assumptions can be a limiting factor because of the extremely unfavourable demographic situation and the inadequate offer of rural households, which are mainly based on the services of accommodation. Proposals for the development of tourism through tourist spots have been given, noting which combination of existing tourist attractions is the best for the further development of every place except Maglić because this settlement has no predisposition for the development of rural tourism. In order to position tourism as an important economic activity and appropriate use of all available resources eight activities which are necessary to be conducted in the future have been proposed.